THERMAL DECOMPOSITION AND KINETIC STUDIES OF TANNIC ACID USING MODEL FREE-METHODS - Ahmad, Naushad; Alam, Manawwer; Naushad, Mu.; Ansari, Anees A.; Alrayes, Basel F.; Alotaibe, Mshari A. (Journal of the Chilean Chemical Society, 2018)
In this manuscript, thermal and kinetic features of a tannic acid was studied by simultaneous TG-DTA techniques in the nitrogen atmosphere at four heating rate. It was observed that thermal decomposition of its constituents occurred in two steps. Model free isoconversional methods namely modified Coast-Redfern (CR), Kissinger-Akahira-Sunose (KAS), Flynn-Wall-Ozawa (FWO) and Freidman (FR) were used for revelation of decomposition kinetics (Ea and lnA) on the whole range of temperature. Mechanisms of decomposition process have been found to follow first order of decomposition rate. Reaction order does not have a substantial effect on the process because of the high value of pre-exponential factor. It was observed that, at the last stage of decomposition process, value of activation energy and pre-exponential factor increased. Decomposition of tannic acid was confirmed by IR spectroscopy.